Designing a Thrifty Approach for SME Business Continuity: Practices for Transparency of the Design Process - Järveläinen Jonna; Niemimaa Marko; Zimmer Markus P. (Association for Information Systems, 2022)
Business continuity (BC) management is an organizational approach to preparing information systems (IS) for incidents, but such approaches are uncommon among small and medium-sized enterprises (SMEs). Past research has indicated a gap in approaches that are designed for SMEs since BC management approaches tend to originate from larger organizations and SMEs lack the resources to implement them. To fill this gap, and to respond to a practical need by an IT consultancy company, we employed design science research (DSR) to develop a BC approach for SMEs coined as the thrifty BC management approach. Jointly with the company’s practitioners, we developed a set of meta-requirements for BC approaches for SMEs anchored in prior BC literature, practitioners’ practical expertise, and the theories of collective mindfulness and sociotechnical systems. We evaluated our thrifty BC management approach with multiple SMEs. These evaluations suggest that the designed approach mostly meets the defined meta-requirements. Moreover, the evaluations offered ample opportunities for learning. The design process, unfolding in a real-world setting, was precarious, rife with contingencies and ad hoc decisions. To render the design process transparent, we adapted four writing conventions from the confessional research genre familiar to ethnographic research but novel to DSR. We offer a threefold contribution. First, we contribute to SMEs’ BC with meta-requirements and their instantiation in a new BC approach (artifact); second, we contribute with four practices of confessional writing for transparency of DSR research; and third, we contribute with reflections on our theoretical learning from throughout the design process.